Politics of nationalism and religion: the experience of Indian sub-continent - Mujahid, Atiqur Rahman; Moniruzzaman, Md. (2018)
European ideas traveled to the Afro-Asian world through colonialism. Among European ideas, the concept of nationalism made the most permanent impact on Afro-Asian continent. This is primarily due to the fact that it enabled non-Europeans to rid themselves of European colonialism. Nationalism is definitely a powerful ideological tool for the subcontinental politics in the germination of anti-colonial movement leading to freedom movement. The idea of nationalism was understood in many ways in the context of modern South Asia. One important aspect of this is that in the evolution of South Asian nationalism religion played a key role. Nationalist groups used religious consciousness, identity, values and symbols in order to mobilize the masses. The main aim of this paper is to explore how nationalism emerged and evolved in the sub-continental political discourse. It examines how nationalism and religion inter-played to split India into a Hindu India and a Muslim Pakistan, and yet again how ethno-nationalism overtook religious identity to split Muslim Pakistan leading to the emergence of a new ethnic-linguistic Bengali Muslim nationalism. Key Words: Bengali nationalism. Hindu nationalism, Indian nationalism, Muslim nationalism, colonialism.